The agrarian reform and communal processes: the communities of the Cahuide and Túpac Amaru SAIS in Peru’s central highlands - Diez Hurtado, Alejandro (2020)
The article analyzes the transformations experienced by a group of communities in the central highlands within the framework of the agrarian reform and the creation of agricultural societies of social interest (SAIS) in the Mantaro valley. It attempts to show that the processes attributed to the changes brought about by the agrarian reform can only be understood with a broader understanding of the processes experienced by the peasant communities in the Mantaro valley. The communal trajectories before, during and after the reform help to understand the processes triggered by the reform and in particular the fate and evolution of the SAIS. Rather than considering associative agriculture as a promoter of technological development in the central highlands, which was cut short by internal contradictions and the actions of Sendero Luminoso, as proposed in previous studies, the idea is to show that the trajectories of the SAIS correspond to the processes that existed before the reform, marked by tensions between the communities and the haciendas, and also between the communities themselves. The article shows, based on the communities that are members of the Cahuide and the Túpac Amaru SAIS –the largest associative enterprises created by the agrarian reform– two different trajectories after the agrarian reform: the first, towards the dissolution of the enterprise and the distribution of its lands, and the second, towards continuity, partial dismemberment and survival in the midst of the crisis.